Implementation of Project-Based Learning: Impact on Metacognitive Awareness and Student Learning Outcomes on Corrosion Materials - Dian Anisa Rokhmah Wati; Retno Eka Pramitasari; Noer Af’idah; Roudhoutul Aulia Rochim; Rahma Ramadhani; Fajar Satriya Hadi; Ahmad Bashri (Jurnal Penelitian Pendidikan IPA, 2025)
The research problem is that students often memorize science concepts without deep understanding, leading to low metacognitive awareness and an inability to solve new problems like corrosion topics. This study aims to measure improvement in metacognitive awareness and cognitive learning outcomes through Project-Based Learning (PjBL). The research method is that a quasi-experimental method with a one-group pretest-posttest design was employed. The participants were fourth-semester mechanical engineering students at UNHASY. Data were collected using a metacognitive awareness questionnaire and a cognitive learning test, administered before and after the PjBL intervention. The data were analyzed quantitatively using a Paired Sample T-Test to determine the significance of the differences between the pretest and posttest scores for both metacognitive awareness and learning outcomes. The research results showed significant improvement in both metacognitive awareness (t=4.70, p<0.05) and learning outcomes (t=4.87, p<0.05). It is concluded that Project-Based Learning is an effective instructional model for fostering metacognitive awareness and improving academic achievement in science education. Its implementation is highly recommended to develop higher-order thinking skills and deeper conceptual understanding.